Fucoidan as a therapeutic agent for ulcerative colitis: mechanisms of action and modulation of the gut microbiota - Zhang, Yating (Frontiers in Cellular and Infection Microbiology, 2025)
Ulcerative colitis (UC), a chronic inflammatory bowel disease driven by gut dysbiosis, immune dysregulation, and oxidative stress, lacks universally effective therapies. Fucoidan (FCD), a sulfated polysaccharide derived from brown algae, has emerged as a multifaceted therapeutic candidate due to its anti-inflammatory, antioxidant, and immunomodulatory properties. This review synthesizes FCD’s mechanisms in UC pathogenesis, emphasizing its suppression of NF-κB and MAPK signaling pathways to reduce proinflammatory cytokines (e.g., IL-6, TNF-α) and regulate TLR-mediated macrophage polarization. FCD enhances intestinal barrier integrity via upregulation of tight junction proteins (Claudin-1, ZO-1) and mucin MUC2 expression, while remodeling gut microbial ecology through enrichment of SCFAs-producing bacteria (e.g., Ruminococcaceae) and suppression of pathogens (Escherichia coli, Candida albicans). Preclinical studies highlight LMWF as a superior candidate, demonstrating enhanced bioavailability and efficacy in mitigating DSS-induced colitis. Despite its promise, challenges persist in structural heterogeneity (source- and extraction-dependent), scalable production of LMWF, and insufficient pharmacokinetic data. Emerging strategies—including nanoparticle-based delivery systems and structural modifications (cross-linking, covalent bonding)—aim to overcome bioavailability limitations. This review underscores FCD’s potential as a functional food or adjuvant therapy for UC, while advocating for rigorous clinical validation to bridge translational gaps, Enrichment of SCFAs-producing taxa and suppression of pathobionts (Escherichia coli, Candida albicans), mediated through prebiotic fermentation. Suppression of NF-κB activation via IκBα stabilization and inhibition of p65 nuclear translocation, and downregulation of MAPK phosphorylation (ERK1/2, JNK, p38), reducing proinflammatory cytokines (IL-6, TNF-α, IL-1β). FCD can be used as a potential treatment for UC.